Impact of the MICA-129Met/Val Dimorphism on NKG2D-Mediated Biological Functions and Disease Risks - Isernhagen, Antje; Malzahn, Dörthe; Bickeböller, Heike; Dressel, Ralf (Frontiers in Immunology, 2016)
The major histocompatibility complex (MHC) class I chain-related A (MICA) is the most polymorphic non-classical MHC class I gene in humans. It encodes a ligand for NKG2D (NK group 2, member D), an activating natural killer (NK) receptor that is expressed mainly on NK cells and CD8+ T cells. The single nucleotide polymorphism (SNP) rs1051792 causing a valine (Val) to methionine (Met) exchange at position 129 of the MICA protein is of specific interest. It separates MICA into isoforms that bind NKG2D with high (Met) and low avidity (Val). Therefore, this SNP has been investigated for associations with infections, autoimmune diseases, and cancer. Here, we systematically review these studies and analyse them in view of new data on the functional consequences of this polymorphism. It has been shown recently, that the MICA-129Met variant elicits a stronger NKG2D signalling, resulting in more degranulation and IFN-γ production in NK cells and in a faster co-stimulation of CD8+ T cells than the MICA-129Val variant. However, the MICA-129Met isoform also down-regulates NKG2D more efficiently than the MICA-129Val isoform. This down-regulation impairs NKG2D-mediated functions at high expression intensities of the MICA-Met variant. These features of the MICA-129Met/Val dimorphism need to be considered when interpreting disease association studies. Particularly, in the field of hematopoietic stem cell transplantation, they help to explain the associations of the SNP with outcome including graft versus host disease and relapse of malignancy. Implications for future disease association studies of the MICA-129Met/Val dimorphism are discussed.